Political Crisis in the Arab Republic of Egypt in 2012 (International relations and international law Journal, 2016)
In this article the reasons, developments and results of the political crisis that took place in Egypt in 2012 are analyzed. In 2012 political situation in the country has turned to be harshly deteriorated, the people have been divided into two political groups. The political conflict between secularists and Islamists has negatively influenced on social and economic situation in the country. But, balance or accord has been ensured between the Islamists and military. Secularist groups failed to shape powerful and organized political parties. Nevertheless, the opposition played big role in the process: the new constitutional decree that gives to president sweeping powers has been refused. This political crisis in Egypt has been finished with the ratification of the new constitution draft in national referendum. The Islamists have proved to all that they have very strong support of society once again. Now, the Freedom and Justice Party led by Mursi should pay a major attention to the economic issues to be successfully settled. The next Parliamentary elections in 2013 might be the last point of this crisis. But, political situation in Egypt might be even worst in the next months. The crisis is still going on. It is too early to state that the Islamists won in this political crisis.
Keywords: Egypt; opposition; Muslim Brotherhood; constitutional decree; constitution draft; crisis; debts; reforms